A fine line : how design strategies are shaping the future of business - Esslinger, Hartmut, 1944- (Jossey-Bass, 2009)
Praise for a fine line. "A breath of turbo-charged fresh air that doesn't regurgitate the ego-maniac CEO's selective memory or an outside expert's misinterpretations. Hartmut explains innovation through the lens of design, and it's about time we gained his valuable perspective."--Guy Kawasaki, former chief evangelist, Apple and co-founder of Alltop.com. "At Flextronics, we fell in love with Hartmut and frog, and their passion for bringing crazy great designs and design processes into the forefront of great product companies. We used their expertise to help our customers, many of